Examining the Relationship Between Cognitive and Social Engagement to Promote Meaningful Learning in High School Chemical Bonding - Suci Milsa Putri; Erlina Erlina; Rachmat Sahputra; Supriatno Salam (Jurnal Pendidikan Sains Indonesia, 2026)
Student engagement plays an important role in supporting effective learning, particularly in learning abstract chemistry concepts such as chemical bonding. This study aimed to analyze students’ cognitive and social engagement and examine the correlation between the two dimensions in chemical bonding learning. The study employed a quantitative descriptive approach with a correlational design. The participants consisted of 32 students enrolled in a chemistry class at a senior high school in Pontianak. Data were collected through questionnaires, classroom observations, and semi-structured interviews. The data were analyzed using descriptive statistics and Spearman Rank correlation analysis. The results showed that students’ cognitive engagement was categorized as very high, with a percentage of 77.97%, while social engagement was also categorized as very high, with a percentage of 80.66%. The highest cognitive engagement indicator was trying to understand mistakes when answering. Furthermore, the correlation analysis revealed a strong positive relationship between cognitive engagement and social engagement (ρ = 0.700, p < 0.001). These findings indicate that students who demonstrate higher cognitive engagement tend to exhibit higher social engagement during chemical bonding learning. Therefore, chemistry teachers should design collaborative learning activities that simultaneously promote conceptual reasoning and peer interaction to enhance meaningful engagement during chemical bonding learning